Redox - Hicks, Peter (New South Wales : Classroom Video, 1991)
Experiments of redox reactions involve the complementary processes of reduction and oxidation
Copy available in DVD format
Executive producer, John Davis
Keywords: Oxidation-reduction reaction; Reduction